Brain networks underlying the processing of sound symbolism related to softness perception - Kitada, Ryo (2021)
Unlike the assumption of modern linguistics, there is non-arbitrary association between sound and meaning in sound symbolic words. Neuroimaging studies have suggested the unique contribution of the superior temporal sulcus to the processing of sound symbolism. However, because these findings are limited to the mapping between sound symbolism and visually presented objects, the processing of sound symbolic information may also involve the sensory-modality dependent mechanisms. Here, we conducted a functional magnetic resonance imaging experiment to test whether the brain regions engaged in the tactile processing of object properties are also involved in mapping sound symbolic information with tactually perceived object properties. Thirty-two healthy subjects conducted a matching task in which they judged the congruency between softness perceived by touch and softness associated with sound symbolic words. Congruency effect was observed in the orbitofrontal cortex, inferior frontal gyrus, insula, medial superior frontal gyrus, cingulate gyrus, and cerebellum. This effect in the insula and medial superior frontal gyri was overlapped with softness-related activity that was separately measured in the same subjects in the tactile experiment. These results indicate that the insula and medial superior frontal gyrus play a role in processing sound symbolic information and relating it to the tactile softness information.